Unravelling Potential Health-Beneficial Properties of Corema album Phenolic Compounds: A Systematic Review - Ana Sofia Cerquido; Martin Vojtek; Rita Ribeiro-Oliveira; Olga Viegas; Joana Beatriz Sousa; Isabel M. P. L. V. O. Ferreira; Carmen Diniz (Pharmaceuticals, 2022)
Corema (C.) album belongs to the family Ericaceae and can be found in the Iberian Peninsula, especially on the coastal areas facing the Atlantic coast. C. album berries have been used for centuries in traditional medicine. Recent studies have revealed that not only the berries but also the leaves have relevant antioxidant, antiproliferative, and anti-inflammatory properties, bringing this plant to the forefront of discussion. A systematic review of the literature was carried out to summarize the phenolic compounds and bioactive properties identified in C. album berries and leaves and to search for research gaps on this topic. The search was conducted in three electronic databases (PubMed, SCOPUS, and Web of Science) using PRISMA methodology. The inclusion criteria were the chemical compositions of the berries, leaves, or their extracts and their bioactive properties. The exclusion criteria were agronomic and archaeological research. The number of studies concerning phenolic compounds’ composition and the bioactive properties of C. album berries and leaves is still limited (11 articles). However, the variety of polyphenolic compounds identified make it possible to infer new insights into their putative mechanism of action towards the suppression of NF-kB transcription factor activation, the modulation of inflammatory mediators/enzymes, the induction of apoptosis, the modulation of mitogen activated protein kinase, cell cycle arrest, and the reduction of oxidative stress. These factors can be of major relevance concerning the future use of C. album as nutraceuticals, food supplements, or medicines. Nevertheless, more scientific evidence concerning C. album’s bioactivity is required.